2004
DOI: 10.1080/00365590410025488
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence and importance of HIV/AIDS and gonorrhea among men aged ≥50 years in the US in the era of erectile dysfunction therapy

Abstract: The past decade saw rises in heterosexual transmission of HIV and i.v. drug use, especially in the population aged >50 years. The CDC reports that the incidence of new HIV infection is stabilizing in men aged 30-39 years and even falling in men aged 20-29 years. Gonorrhea is well known to increase infectivity for HIV and other STDs. Although the rates of gonorrhea infection fell throughout the early 1990s, they increased by 9% between 1997 and 1999. The number of sildenafil prescriptions has increased by almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 5 publications
1
36
0
Order By: Relevance
“…100 Effective treatment of ED can increase the risk of spreading HIV. 101 Benotschet al 102 have shown that men who took phosphodiesterase-5 inhibitors had higher rates of sexually risky behavior. This observation means that there might be an ethical dilemma in treating ED in HIV-positive patients.…”
Section: Sexual Dysfunction and Infertility In Patients With Hiv And mentioning
confidence: 99%
“…100 Effective treatment of ED can increase the risk of spreading HIV. 101 Benotschet al 102 have shown that men who took phosphodiesterase-5 inhibitors had higher rates of sexually risky behavior. This observation means that there might be an ethical dilemma in treating ED in HIV-positive patients.…”
Section: Sexual Dysfunction and Infertility In Patients With Hiv And mentioning
confidence: 99%
“…The use of oral phosphodiesterase type 5 (PDE5) inhibitor medications, such as sildenafil (Viagra ® ), has changed the medical management of ED and allowed men with ED to resume and once again enjoy sexual activity (Dorsey, Keel, Klavens, & Hellstrom, 2010;Karlovsky, Lebed, & Mydlo, 2004).…”
Section: Background and Significancementioning
confidence: 99%
“…Older adults are as at risk or at higher risk for contracting HIV/AIDS as younger populations when they engage in risky behaviors such as unprotected sex and alcohol and drug use [2,7,16]. In fact, the major reasons for exposure to AIDS in those older than 50 years of age who are living with AIDS are: male homosexual transmission (46%), intravenous drug use (29%), heterosexual transmission (18%), and unknown factors (7%) [2,3].…”
mentioning
confidence: 99%